2019
DOI: 10.1186/s13071-019-3527-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of injectable toltrazuril-iron combination product and oral toltrazuril against early experimental infection of suckling piglets with Cystoisospora suis

Abstract: Background Toltrazuril is frequently administered for the metaphylactic control of piglet cystoisosporosis. In a previous study, the efficacy of parenteral toltrazuril (45 mg/piglet, Group Forceris®) applied on the 2nd day of life (dol), and of oral toltrazuril (20 mg/kg of body weight, Group Baycox®) applied on the 4th dol was evaluated in an experimental model with Cystoisospora suis infection on the 3rd dol (late infection, LI). In a follow-up study, efficacy and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Parasite propagation and study design, including experimental infection and treatment, were previously described (Joachim et al, 2019) with additional fecal samplings for microbiota analysis. In brief, 38 conventionally raised piglets (Landrace × Large White) from three crossbred sows were randomly allocated to three treatment groups.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasite propagation and study design, including experimental infection and treatment, were previously described (Joachim et al, 2019) with additional fecal samplings for microbiota analysis. In brief, 38 conventionally raised piglets (Landrace × Large White) from three crossbred sows were randomly allocated to three treatment groups.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…Impaired intestinal homeostasis and slow regeneration of the intestinal epithelium in infected piglets lead to significant reductions in body weight gain, most likely due to reduced nutrient absorption (Mundt et al, 2003(Mundt et al, , 2006Joachim and Mundt, 2011). The disease is effectively controlled by oral or parenteral administration of a single dose of the triazinone toltrazuril during the developmental phase of C. suis in the host (Mundt et al, 2006;Joachim et al, 2018cJoachim et al, , 2019. The exact mode of action of toltrazuril is not known but it has been suggested that toltrazuril interferes with nuclear division and mitochondrial activity in coccidian parasites (Harder and Haberkorn, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Oocyst excretion is a primary parameter to estimate the intensity and clinical presentation of C. suis infection [23]. Detailed results of the clinical and parasitological outcome of experimental infections of the involved animals have been published previously [7]. Briefly, three groups of piglets (n=11-13 animals/group) were used.…”
Section: Clinical and Parasitological Outcome Of Experimental Infectionsmentioning
confidence: 99%
“…Parasite propagation and study design, including experimental infection and treatment, were previously described [7] with additional fecal samplings for microbiota analysis. In brief, 38 conventionally raised piglets (Landrace x Large White) from three crossbred sows were randomly allocated to three treatment groups.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation